2015
DOI: 10.1007/s13592-014-0342-x
|View full text |Cite
|
Sign up to set email alerts
|

Odor learning and odor discrimination of bees selected for enhanced hygienic behavior

Abstract: -Odor learning and odor discrimination were tested in a line of honeybees selected for increased hygienic behavior (HB) against the Varroa mite and compared with control bees (CB). Olfactory proboscis extension conditioning was used to quantify learning, discrimination, and generalization. Retention tests were performed after 1 h and after 1 day to probe the stability of memory. HB and CB did not differ in their learning, discriminating, generalizing, and remembering behavior when pairs of floral odors and pai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 52 publications
0
20
0
Order By: Relevance
“…Social immunity2 is likely to play a major role as resistance mechanism; for instance, adult honey bee workers cooperate to detect and remove worker brood infested by this mite, thereby interrupting its reproduction612. The trigger of this hygienic behaviour by workers is based on signals from infested brood13 and/or by cues from the parasite14, on the ability of workers to detect this information as well as on their response thresholds111516. The ability of A. cerana workers to perform hygienic behaviour towards V. destructor -infested brood is greater than that of the new host, A. mellifera 17.…”
mentioning
confidence: 99%
“…Social immunity2 is likely to play a major role as resistance mechanism; for instance, adult honey bee workers cooperate to detect and remove worker brood infested by this mite, thereby interrupting its reproduction612. The trigger of this hygienic behaviour by workers is based on signals from infested brood13 and/or by cues from the parasite14, on the ability of workers to detect this information as well as on their response thresholds111516. The ability of A. cerana workers to perform hygienic behaviour towards V. destructor -infested brood is greater than that of the new host, A. mellifera 17.…”
mentioning
confidence: 99%
“…There is a large body of evidence suggesting that hygienic bees identify diseased brood through olfactory cues891011121314 and that they are more sensitive to and better at discriminating between them814. The antennae, bees’ main olfactory organ15, have been shown to play a pivotal role in HB with multiple independent research groups identifying significantly differentially expressed antennal genes in hygienic versus non-hygienic bees, as well as strong antennal biomarkers for selective breeding913161718.…”
mentioning
confidence: 99%
“…Learning may be a component of specialisation that influences the efficiency on this task performance; as occurred with other out-hive-tasks (Dukas & Visscher, 1994). In fact, a recent study showed that honeybees selected for increased hygienic behaviour against V. destructor performed better in learning and discriminating between the volatile odors of Varroa-infected and non-infected pupae than honeybees from the control colonies (Chakroborty, Bienefeld, & Menzel, 2015). If the learning capacity of bees has a genetic basis, then the temporal persistence to identify abnormal odours from the brood observed in our H colony could be associated with a higher learning capacity in these bees.…”
Section: Discussionmentioning
confidence: 99%
“…Subgroups of honeybees in a colony that start engaging in a certain task, are likely to have a similar response threshold for a certain stimulus associated with that task and will constitute a task group (Page et al, 2006). In particular, the genetic propensity of individual bees (or a task group) to perform hygienic behaviour is explained by their high responsiveness to odour cues that stimulate them to initiate the hygienic activities (Masterman, Smith, & Spivak, 2000;Masterman et al, 2001;Spivak et al 2003;Swanson et al, 2009;Palacio et al, 2010;Chakroborty, Bienefeld, & Menzel, 2015). Previous studies detected that hygienic bees show increased olfactory sensitivity and responsiveness to the odours of diseased brood compared to non-hygienic bees (Masterman, Smith, & Spivak, 2000;Masterman et al, 2001;Spivak et al, 2003;Palacio et al, 2010).…”
mentioning
confidence: 99%